2009
DOI: 10.1590/s0101-31222009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Conservação de sementes de Magnolia ovata St. Hil

Abstract: RESUMO -A pesquisa foi regularizada com o objetivo de estudar a influência do teor de água da semente e da temperatura de armazenamento sobre a conservação das sementes de Magnolia ovata (Magnoliaceae), uma árvore nativa brasileira. Para tanto, sementes recém colhidas com 23,5% de água foram submetidas à secagem para a obtenção de sementes com os teores de água de 17,4%, 10,9% e 7,1%. Em seguida, as sementes foram acondicionadas em sacos de polietileno e armazenadas a 15ºC e a 20ºC. As sementes foram armazenad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Thus, there is an increase in seed vigor at the beginning of the reduction of moisture. Pupim et al (2009) andFaria et al (2004) also observed an increase in the physiologic potential of Magnolia ovata and Inga vera at the beginning of drying, and attributed this increase to the continued maturation during the drying period.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, there is an increase in seed vigor at the beginning of the reduction of moisture. Pupim et al (2009) andFaria et al (2004) also observed an increase in the physiologic potential of Magnolia ovata and Inga vera at the beginning of drying, and attributed this increase to the continued maturation during the drying period.…”
Section: Resultsmentioning
confidence: 95%
“…Magnolia ovata (Magnoliaceae) is a native forest tree used for recuperation of areas near rivers; it produces recalcitrant seeds (23.5% water content) that lose viability after 30 d storage. In contrast, viability was maintained for 60 d (starting at 30%, decreasing to 23%, compared to initial germination rate) in seeds dehydrated to 10.9% water content and stored at 15°C or 20°C (Pupim et al 2009). Another Magnoliaceae, Talauma ovata, was also classified as recalcitrant by Carvalho et al (2006).…”
Section: Progress and Incentives For Recalcitrant Seed Conservation Imentioning
confidence: 98%